The Date Palm (Phoenix dactylifera L.) Fibre as a Biomonitor of Lead and Other Elementals in Arid Environments - al-Shayeb, S.M.; Seaward, M.R.D. (Asian Journal of Chemistry, 2010)
The fibre of date palm (Phoenix dactylifera L.) has been tested as a possible biomonitor of lead and other metal pollution in Riyadh City, Saudi Arabia. The content of (Ph, Zn, Cu, Ni, Cr and Li) was determined for washed and unwashed fibre samples collected from three different sites with different degrees of metal pollution (urban, rural area with sludge amended soils and rural "control" area). Differences between washed and unwashed samples revealed that the large amount of metal pollutants exist as superficial contaminants, which varied according to the metal source. However, P. dactylifera fibres were found to be suitable biomonitor for metal pollution in Riyadh and similar arid and semi-arid environments.